Strategies to Optimize Performance of Lithium-Ion Supercapacitors: Screening of Cathode Configuration, Anode Pre-Lithiation Loading and Separator Type. (10th February 2015) - Cao, Wanjun; Li, Yangxing; Fitch, Brian; Shih, Jonathan; Doung, T; Zheng, Jim P
Abstract : The Li-ion capacitor (LIC) is composed of a lithium-doped carbon anode and an activated carbon cathode, which is a half Li-ion battery (LIB) and a half electrochemical double-layer capacitor (EDLC). LICs can achieve much more energy density than EDLC without sacrificing the high power performance advantage of capacitors over batteries. LIC pouch cells were assembled using activated carbon (AC) cathode and hard carbon (HC) + stabilized lithium metal power (SLMP ® ) anode. Different cathode configurations, various SLMP loadings on HC anode, and two types of separators were investigated to achieve the optimal electrochemical performance of the LIC. Firstly, the cathode binders study suggests that the PTFE binder offers improved energy and power performances for LIC in comparison to PVDF. Secondly, the mass ratio of SLMP to HC is at 1:7 to obtain the optimized electrochemical performance for LIC among all the various studied mass ratios between lithium loading amounts and active anode material. Finally, compared to the separator Celgard PP 3501, cellulose based TF40-30 is proven to be a preferred separator for LIC.